Is PML a tumor suppressor? - Massimiliano eMazza; Pier Giuseppe ePelicci (Frontiers in Oncology, 2013)
The role of the promyelocytic leukemia protein (PML) has been widely tested in many different contexts, as attested by the hundreds of papers present in the literature. In most of these studies, PML is regarded as a tumor suppressor, a notion on the whole accepted by the scientific community. In this review, we examine how the concept of tumor suppressor gene has evolved until now and then systematically assess whether this assumption for PML is supported by unambiguous experimental evidence.